2013
DOI: 10.1080/02646838.2013.845873
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological distress during pregnancy on early postpartum weight retention

Abstract: Background: Pregnancy has been identified as a risk factor for increasing rates of obesity in women. In recent years, psychological factors have been demonstrated to play a key role in contributing to and maintaining postpartum weight retention (PWR). Objective: The aim of this study was to explore the relationship between psychological distress during late pregnancy and early postpartum, specifically depression, anxiety, stress, and body dissatisfaction, and early PWR. Methods: Pregnant women (N = 227) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 44 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…No study included population-based representative samples or reported cross-national data. Seven publications reported on the association between pregnancy obesity and anxiety (Bogaerts et al, 2013a(Bogaerts et al, , 2013bCarter et al, 2000;Catov et al, 2010;Harville et al, 2009;Laraia et al, 2009;McPhie et al, 2015), two on the association between excessive GWG and anxiety Webb et al, 2009), and three on the association between PPWR and anxiety (Bogaerts et al, 2013c;Phillips et al, 2014aPhillips et al, , 2014b. 10 Studies had prospective designs (Bogaerts et al, 2013a(Bogaerts et al, , 2013cCarter et al, 2000;Catov et al, 2010;Harville et al, 2009;Laraia et al, 2009;McPhie et al, 2015;Phillips et al, 2014aPhillips et al, , 2014bWebb et al, 2009), but some publications based on prospective designs only reported data from one time point (Catov et al, 2010;Laraia et al, 2009).…”
Section: Description Of Included Studiesmentioning
confidence: 95%
See 3 more Smart Citations
“…No study included population-based representative samples or reported cross-national data. Seven publications reported on the association between pregnancy obesity and anxiety (Bogaerts et al, 2013a(Bogaerts et al, , 2013bCarter et al, 2000;Catov et al, 2010;Harville et al, 2009;Laraia et al, 2009;McPhie et al, 2015), two on the association between excessive GWG and anxiety Webb et al, 2009), and three on the association between PPWR and anxiety (Bogaerts et al, 2013c;Phillips et al, 2014aPhillips et al, , 2014b. 10 Studies had prospective designs (Bogaerts et al, 2013a(Bogaerts et al, , 2013cCarter et al, 2000;Catov et al, 2010;Harville et al, 2009;Laraia et al, 2009;McPhie et al, 2015;Phillips et al, 2014aPhillips et al, , 2014bWebb et al, 2009), but some publications based on prospective designs only reported data from one time point (Catov et al, 2010;Laraia et al, 2009).…”
Section: Description Of Included Studiesmentioning
confidence: 95%
“…Three publications reported on associations between anxiety and PPWR (Bogaerts et al, 2013c;Phillips et al, 2014aPhillips et al, , 2014b ( Table 2). In all studies, PPWR was calculated as the difference between self-reported postpartum weight and retrospectively self- reported pre-pregnancy weight.…”
Section: Assessment and Definition Of Ppwr And Anxietymentioning
confidence: 97%
See 2 more Smart Citations
“…Phillips et al [28] studied weight during pregnancy and the postpartum period. Weight gain was detected extremely early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%